El Tractado de caso y fortuna de Lope de Barrientos. El arte de gobernar bajo el signo de la suerte inescrutable - Mianda Cioba (Revista de Istorie și Teorie Literară)
During the tormented fifteenth century, the symbolic legitimation of royal power through discourse contains a rapid succession of ideological models impelled by the political and moral crisis of authority: from royalty conceived as a providential instrument of the divine project, to the political functionalism, organized around the newly discovered concept of reason of State. The debate is undertaken within the framework of what F. Gómez Redondo calls “the order of the royal culture”, an ordo regis that supposes the duty to act in accordance with a project of common good, which relies on the separation between the person of the king and the authority that he represents. The Tractado de caso y fortuna of Lope de Barrientos, preceded by the Laberinto de Fortuna of Juan de Mena and by the Compendio de la Fortuna of Martín de Córdoba, the Libro de los Pensamientos Variables of Pedro Gracia Dei and other treatises of practical philosophy and politics of the same period are works subject to the complex debate on the foundations of the king’s authority. Through these texts, the Fortune of humanists is identified, on the one hand, with a poetic category describing the dramatic condition of the individual who seeks to understand the mysterious character of human acts and their consequences, and on the other, with a political concept about a new way of approaching the experience of governance understood as a difficult negotiation between the manifestation of casualty and the rational intervention in the development of historical facts.